2013
DOI: 10.4236/jamp.2013.16008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noncircular Inlet on the Flow Structures in Turbulent Jets

Abstract: Turbulent jet flows with noncircular nozzle inlet are investigated by using a Reynolds Stress Model. In order to analyze the effects of noncircular inlet, the cross section of inlet are selected as circular, square, and equilateral triangular shape. The jet half-width, vorticity thickness, and developments of the secondary flow are presented. From the result, it is confirmed that the secondary flows of square and equilateral triangular nozzle are more vigorous than that of the circular jet. This development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…be attributed to smaller length of the potential core for triangular jet. Kim and Park [11] report that the potential core length is around 7.8d e for triangular free jet, 8.4d e for square free jet and 9.8d e for circular free jet at a Reynolds number of 21,000. Singh et al [10] corroborate this by reporting higher decay rates for triangular and square free jets compared to that of circular free jets at a Reynolds number of 7200.…”
Section: Influence Of Nozzle Shape On Heat Transfermentioning
confidence: 98%
See 3 more Smart Citations
“…be attributed to smaller length of the potential core for triangular jet. Kim and Park [11] report that the potential core length is around 7.8d e for triangular free jet, 8.4d e for square free jet and 9.8d e for circular free jet at a Reynolds number of 21,000. Singh et al [10] corroborate this by reporting higher decay rates for triangular and square free jets compared to that of circular free jets at a Reynolds number of 7200.…”
Section: Influence Of Nozzle Shape On Heat Transfermentioning
confidence: 98%
“…The local heat transfer distribution over the impingement plate shows axis switching of jet by counter flow vortices which are present at the corners of noncircular nozzles. Kim and Park [11] reported development of axial flow distribution for circular, square and triangular shapes at different z/d e by contour plots. Present Nusselt number contour plots are in good correlation with the results reported by Kim and Park [11] at corresponding z/d e .…”
Section: Influence Of Nozzle Shape On Heat Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology helped in determining the equivalence ratio which effectively induce secondary flow (Hoke et al 2002). The effect of different geometrical configurations of primary flow inlets on the turbulent flow regime of jets was investigated using Reynolds Stress Model and it was concluded that development of the triangular jets is stronger than others (Kim and Park, 2013).…”
Section: Introductionmentioning
confidence: 99%